One-Pot Synthesis of High-Flux b-Oriented MFI Zeolite Membranes for Xe Recovery - Wang, Xuerui (ACS Appl Mater Interfaces, 2018)
[Image: see text] We demonstrate that b-oriented MFI (Mobil Five) zeolite membranes can be manufactured by in situ crystallization using an intermediate amorphous SiO(2) layer. The improved in-plane growth by using a zeolite growth modifier leads to fusion of independent crystals and eliminates boundary gaps, giving good selectivity in the separation of CO(2)/Xe mixtures. The fast diffusion of CO(2) dominates the overall membrane selectivity toward the CO(2)/Xe mixture. Because of the straight and short [010] channels, the obtained CO(2) permeation fluxes are several orders of magnitude higher than those of carbon molecular sieving membranes and polymeric membranes, opening opportunities for Xe recovery from waste anesthetic gas.